Pengembangan Media Pembelajaran Sejarah Indonesia Berbasis Game Edukasi Untuk Siswa Kelas 7 Madrasah Tsanawiyah Al-Hafizh Rajeg - Fiqih Hana Saputri; Gharifa Al Ikhsan Ananda Putra (Universitas Islam Raden Rahmat, Malang, 2024)
MTs Al-Hafizh Rajeg is a school located in Tangerang. The lack of knowledge among students about Indonesian history is a current issue. Therefore, a mobile-based Indonesian history learning media was developed to facilitate students' history learning. The research objective is to create an educational game about Indonesian history that enhances the interest and understanding of MTs Al-Hafizh Rajeg students in the subject of Civic Education. The Waterfall Method was used in this study. Construct 2 was employed to create engaging, interactive, and user-friendly learning media. Based on the satisfaction survey results with 10 respondents, it can be concluded that the Indonesian History learning media has achieved a high level of satisfaction, with a 95% satisfaction rate. Overall, the development of this Indonesian history educational game has great potential to improve the interest and understanding of MTs Al-Hafizh Rajeg students in the subject of Civic Education.